IFPRI research and engagement: Climate change and agrifood systems - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Climate change poses unprecedented challenges to the world’s food systems. Rising temperatures, changing rainfall patterns, and more frequent extreme weather events threaten agricultural production and the biodiversity and ecosystem services that underpin agriculture. Within food systems, climate change affects processing, storage, transport, and retailing of food and affects our food environments. These growing climate risks impact food security, nutrition, and human health, as well as equity and livelihoods, with poor food producers and consumers hit hardest. They make food systems a riskier source of income and reduce the availability of food — worsening poverty and inequity, disrupting livelihoods, and contributing to hunger and malnutrition. At the same time, food systems are failing to provide healthy diets for all, and are generating one-third of human-caused greenhouse gases. Solutions must address this complex nexus of problems. Climate change adaptation and resilience-building efforts for food systems must be accelerated to reverse growing malnutrition, ensure that all people can access healthy diets, and provide sustainable livelihoods. At the same time, efforts to transform food systems work to reduce their environmental footprint. Farmers and small businesses along food value chains in low- and middle-income countries will have to adapt their practices to a climate marked by extreme weather events and changing seasonal patterns in order to meet growing and changing food demand, while also contributing to mitigation. Support for this critical transformation requires not only the development, dissemination, and adoption of appropriate low-emissions, climate-smart technologies and practices, but also a focus on the policies, institutions, governance, and behavior change that can promote sustainable, inclusive food systems.